Bentuk Komunikasi Simbolik Pada Prosesi Maperas Dalam Upacara Potong Gigi Di Desa Alasangker Kecamatan Buleleng Kabupaten Buleleng - Kadek Soni Sumartini; Putu Sanjaya (Pramana: Jurnal Hasil Penelitian, 2022)
The Teeth Cutting Ceremony or Mapandes is one part of the Manusa Yajña ceremony which is generally carried out when a person begins to grow up to be a teenager or adult. In general, the implementation of the tooth-cutting ceremony in the Alasangker village of Buleleng District, Buleleng Regency in general is the same as the implementation of the Tooth Cutting ceremony in other places, both in the procession and in the ceremony. However, there is one ritual procession that is tucked away in the tooth-cutting ceremony in Alasangker Village, namely the Maperas ritual procession. In the Maperas procession there is a symbolic conversation between parents and children during the ceremony. The symbolic communication that occurs between parents and children in this Maperas ritual is an interaction that occurs both verbally and non-verbally with a religious nuance. The religious nuance is because there are moral messages contained in it.